Pelatihan Kewirausahaan Berbasis Digital bagi Siswa Disabilitas SLB PGRI Kamal Kabupaten Bangkalan - Putri Ulfa Kamalia; Muhammad Abdul Ghofur; Riza Yonisa Kurniawan; Retno Mustika Dewi; Fitrania Maghfiroh; Asmaul Khusnah (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2023)
The implementation of this community service aims to improve the ability of students with disabilities to prepare digital-based business plans and marketing. This service method uses training, which consists of the introduction activity stage of market research and identification of business opportunities, the action stage for implementing the business plan and the evaluation stage. The evaluation instrument for this activity uses a questionnaire and is analyzed descriptively. The results of this community service show: 1) the entrepreneurial abilities of students with disabilities have increased; 2) the knowledge of students with disabilities regarding digital business opportunities increases; 3) the knowledge of disabled students regarding business planning using the Business Model Canvas (BMC) increases; and 4) knowledge of students with disabilities regarding digital promotion and marketing methods increases so that they are able to market products through social media and market places.